Mining at Pozarrate: Applying Experimental Approaches to Understand the Neolithic Extraction of Flint in the Sierra de Araico (Treviño, Spain) - Hugo H. Hernández; Cristina López-Tascón; Mikel Aguirre; Antonio Tarriño (EXARC Journal, 2020)
The aim of this paper is to introduce the scientific works performed in the Sierra de Araico Neolithic Mining Complex, mainly located in the Treviño enclave of Spain, in the Basque-Cantabrian Basin, between Burgos and Álava provinces. Archaeological works were focused on the Pozarrate quarry, dated to the Neolithic period (6000-5600 BP). This site is unique since it has been used recently to intensively dig out high-quality flint cores. This type of flint, called Treviño, has had wide circulation in archaeological sites of the Cantabrian Mountains and Western Pyrenees. The interdisciplinary research applied to Pozarrate site involves LiDAR analysis and geological, procurement, typological, technological and functional research related to flint blanks and different mining tools manufactured on the local flint. The research also includes the study of other raw materials, such as dolerite hammer stones and antler picks. Different experiments, related to the comprehension of mining processes, have been carried out in order to clarify the archaeological findings of the site. Particularly, we present the results of an experiment on flint changes produced by contact with fire and an experiment on the replication, utility and use-life of hammer stones used to dig out the flint cores.